Student-Centered Curriculum Innovation in the Digital Age - Yenni Novita Harahap; Emilda Sulasmi (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2026)
The digital era requires education systems to innovate curricula that are adaptive, relevant, and oriented toward learners’ needs in order to optimally develop 21st-century competencies. This study aims to analyze the concept of learner-needs-based curriculum innovation, its forms of implementation in digital learning processes, as well as the challenges and opportunities faced by educational institutions. This research employs a literature review approach by examining national and international journal articles published within the last five years that discuss personalized learning, educational technology integration, and the strengthening of students’ digital competencies. The findings indicate that curriculum innovation in the digital era does not merely emphasize technological integration, but also involves the recontextualization of learning objectives, content, and strategies to align with students’ characteristics, interests, and learning styles. Needs-based curricula have been shown to promote more participatory, collaborative, and meaningful learning through differentiation, project-based learning, and the use of digital platforms. Nevertheless, its implementation is still constrained by teachers’ limited digital literacy, infrastructure readiness, and disparities in technological access. This study concludes that curriculum innovation must be supported by continuous teacher capacity development, sustainable institutional policies, and collaboration among schools, government, and the wider community to build an inclusive digital learning ecosystem that is responsive to learners’ needs.